PENGEMBANGAN TEPUNG UBI UNGU DAN SUSU KACANG KEDELAI SEBAGAI ALTERNATIF SNACK PUDING BAGI PENDERITA DIABETES MELITUS TIPE 2 - Marianawati Saragih; F. Agung Suprihartono; Roro Nur Fauziyah; Nuniek Widyaningrum; Jedya Lucas A. Purba (Jurnal Gizi dan Dietetik, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder that requires a regular dietary regimen, including the selection of low-sugar snacks that align with daily energy requirements. Snacks for individuals with diabetes should contribute 10–15% of total energy needs, equivalent to 120–180 kcal from a 1200-kcal diet. The availability of low-sugar snack products remains limited, indicating the need for innovations using local food ingredients that are safe for consumption. Purple sweet potato flour and soy milk contain fiber, anthocyanins, and plant-based protein and are naturally low in sugar, making them suitable as ingredients for diabetes-friendly snacks. This study aimed to develop a low-sugar pudding snack made from purple sweet potato flour and soy milk with the addition of sugar-free fla, and to assess its organoleptic properties, combined nutritional composition, and production cost. The best formulation (F3) contained 65.27 kcal, 2.41 g protein, 1.0 g fat, 11.6 g carbohydrates, 1.2 g fiber, and 0.18 g sugar per 100 g. The sugar-free fla contributed an additional 73 kcal, 9.06 g protein, 5.14 g fat, and 2.32 g carbohydrates. The total energy of the product was approximately 138 kcal per serving, meeting the recommended energy criteria for snacks for individuals with type 2 diabetes. Sensory evaluation indicated that F3 was the most preferred formulation. The production cost per serving was IDR 6,050. In conclusion, this low-sugar pudding with sugar-free fla is a nutritious, safe, and energy-appropriate snack alternative for individuals with type 2 diabetes mellitus